2017
DOI: 10.2175/106143016x14733681696167
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation of Tartrazine and Brilliant Blue with Pulsed Ultraviolet Light Emitting Diodes

Abstract: This study investigated the effect of ultraviolet light-emitting diodes (UVLEDs) coupled with hydrogen peroxide as an advanced oxidation process (AOP) for the degradation of two test chemicals. Brilliant Blue FCF consistently exhibited greater degradation than tartrazine, with 83% degradation after 300 minutes at the 100% duty cycle compared with only 17% degradation of tartrazine under the same conditions. These differences are attributable to the structural properties of the compounds. Duty cycle was positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Scott et al reported the oxidative degradation under UV light of Tz and BB, which resulted in a slow process. After 300 min of UV light exposure, 83% of BB and only 17% of Tz underwent degradation [47]. Taking into account that using silver nanoparticles as catalysts of the degradation reactions of the above mentioned dyes, Tz concentration lowered by 26% after 45 min of reaction and 97% of BB was removed after 15 min, is highly recommended to use the catalytic degradation of these dyes instead of their UV light mediated oxidation.…”
Section: Dye Reducing Catalytic Activity Of Agnpsmentioning
confidence: 99%
“…Scott et al reported the oxidative degradation under UV light of Tz and BB, which resulted in a slow process. After 300 min of UV light exposure, 83% of BB and only 17% of Tz underwent degradation [47]. Taking into account that using silver nanoparticles as catalysts of the degradation reactions of the above mentioned dyes, Tz concentration lowered by 26% after 45 min of reaction and 97% of BB was removed after 15 min, is highly recommended to use the catalytic degradation of these dyes instead of their UV light mediated oxidation.…”
Section: Dye Reducing Catalytic Activity Of Agnpsmentioning
confidence: 99%
“…Similarly, Scott et al. (2017) studied the degradation of tartrazine and Brilliant Blue in solutions containing hydrogen peroxide exposed to UV light; here again, the hydroxyl radicals produced catalyzed the reaction and could serve as a means for removing the colorants from wastewater. These studies were attempting to intentionally decolorize the solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Oancea and Meltzer (2014) reported fast degradation of tartrazine in solutions containing hydrogen peroxide; upon UV light exposure, hydrogen peroxide F I G U R E 1 Degradation of tartrazine in iron-containing solutions at pH 3 and 30°C as affected by UV light exposure (365 nm, 39 μW/cm 2 ) modeled via pseudo-first-order kinetics F I G U R E 2 Degradation of Allura Red in 0.05 M citrate buffer and water with and without 3.6 ppm iron at pH 3 and 30°C during UV light exposure (365 nm, 39 μW/cm 2 ) modeled via pseudo-zeroorder kinetics undergoes photolysis to yield hydroxyl radicals that react with tartrazine. Similarly, Scott et al (2017) studied the degradation of tartrazine and Brilliant Blue in solutions containing hydrogen peroxide exposed to UV light; here again, the hydroxyl radicals produced catalyzed the reaction and could serve as a means for removing the colorants from wastewater. These studies were attempting to intentionally decolorize the solutions.…”
Section: Colorant Stability Upon Uv Light Exposurementioning
confidence: 99%
“…To compare the reactivity of the K 2 S 2 O 8 /AgNPs system, the degradation % and rate constants of different dyes with H 2 O 2 and other metal NPs are summarized in Table . It is well known that the experimental conditions such as the type of irradiation and metal NPs have significant impact on the degradation of dyes. K 2 S 2 O 8 /AgNPs is found to be more active to the E133 degradation compared to others. AgNPs activate the peroxide bond of S 2 O 8 2– and generate the oxygen reactive species (SO 4 · – and HO · ), which might be responsible for the degradation of toxic wastewater pollutants.…”
Section: Resultsmentioning
confidence: 99%